2021
DOI: 10.3390/foods10092102
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Characterization of Olive Oils from the North Aegean Region Based on the Analysis of Biophenols with UHPLC-QTOF-MS

Abstract: Olive oil is famous due to the nutritional properties and beneficial health effects. The exceptional properties of virgin (VOO) and extra virgin olive oil (EVOO) are credited to the bioactive constituents of their polar fraction, the phenolic compounds. The concentration and composition of biophenols can be influenced by the geographical origin, the cultivar, as well as several agronomic and technological parameters. In this study, an ultra-high-performance liquid chromatography coupled to quadrupole-time of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 67 publications
0
9
0
1
Order By: Relevance
“…With FIA-MRMS, statistically significant compounds and chemical classes were identified as markers of quality and authenticity and associated with specific EVOO characteristics, i.e., geographic region, cultivation practice, and manufacturing procedure. Very recently, Kritokou et al, 2021 [ 134 ], found significant differences between Greek EVOOs from five islands originating from the North Aegean Region (Chios, Fournoi, Ikaria, Lesvos, and Samos) using the UHPLC-QTOF-MS method. The biophenol contents were analysed to investigate discriminations between different regions.…”
Section: Mass Spectrometry (Ms)-based Studiesmentioning
confidence: 99%
“…With FIA-MRMS, statistically significant compounds and chemical classes were identified as markers of quality and authenticity and associated with specific EVOO characteristics, i.e., geographic region, cultivation practice, and manufacturing procedure. Very recently, Kritokou et al, 2021 [ 134 ], found significant differences between Greek EVOOs from five islands originating from the North Aegean Region (Chios, Fournoi, Ikaria, Lesvos, and Samos) using the UHPLC-QTOF-MS method. The biophenol contents were analysed to investigate discriminations between different regions.…”
Section: Mass Spectrometry (Ms)-based Studiesmentioning
confidence: 99%
“…Among edible oils, virgin olive oil (VOO) and, especially, extra-virgin olive oil (EVOO) present important and outstanding characteristics due to their differentiated sensory qualities (taste and aroma) and high nutritional value, which is associated with their high content of natural antioxidants, such as carotenoids, phytosterols, flavonoids, α-tocopherol and other phenolic compounds [ 1 , 2 ]. The consumption of VOO and EVOO shows numerous health benefits, including lowering of LDL cholesterol, as well as protection against diseases such as cancer, obesity, diabetes, kidney, neurodegenerative and cardiovascular diseases due to their antioxidant, anti-inflammatory, antiviral and antimicrobial properties [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Em cinco ilhas do Mar Egeu foram determinados biofenóis em azeites extra virgens gregos, através de cromatografia líquida de ultra-alto desempenho. Diferenças significativas foram encontradas entre as ilhas com base no conteúdo fenólico geral e também nos níveis de concentração de compostos individuais, comprovando novamente que a composição de biofenóis podem ser influenciadas pela origem geográfica, cultivar, bem como por parâmetros tecnológicos e agronômicos (Kritikou et al, 2021).…”
Section: Journal Of Theunclassified